2020
DOI: 10.1111/tpj.14950
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the domestication‐shaped genetic architecture of lettuce primary metabolism

Abstract: Lettuce (Lactuca sativa L.) is an important vegetable crop species worldwide. The primary metabolism of this species is essential for its growth, development and reproduction as well as providing a considerable direct source of energy and nutrition for humans. Here, through investigating 77 primary metabolites in 189 accessions including all major horticultural types and wild lettuce L. serriola we showed that the metabolites in L. serriola were different from those in cultivated lettuce. The findings were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 73 publications
(121 reference statements)
1
33
0
Order By: Relevance
“…Moreover, the study by Zhu et al revealed that breeding for pink fruits, favored by Asian consumers, also modified the content of >100 metabolites, whereas the introgression of resistance genes from wild relatives also caused unexpected disturbance to the metabolome (Figure 2). Study of the primary metabolite complement of the lettuce population described previously revealed that metabolites in the wild species L. serriola differed from those of all evaluated cultivated lettuces, supporting a single domestication event for this species [99]. Moreover, galactinol, raffinose, malate, quinate, and threonate were affected by the domestication and cultivar differentiation processes, with the first two metabolites likely being selected during stem lettuce cultivation as an adaptation to the environment in China.…”
Section: Open Accessmentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, the study by Zhu et al revealed that breeding for pink fruits, favored by Asian consumers, also modified the content of >100 metabolites, whereas the introgression of resistance genes from wild relatives also caused unexpected disturbance to the metabolome (Figure 2). Study of the primary metabolite complement of the lettuce population described previously revealed that metabolites in the wild species L. serriola differed from those of all evaluated cultivated lettuces, supporting a single domestication event for this species [99]. Moreover, galactinol, raffinose, malate, quinate, and threonate were affected by the domestication and cultivar differentiation processes, with the first two metabolites likely being selected during stem lettuce cultivation as an adaptation to the environment in China.…”
Section: Open Accessmentioning
confidence: 80%
“…Although many studies have been carried out in cereals, a wide range of non-grass studies have been performed, providing insight into the metabolic changes that occurred during domestication of a range of other species including tomato [54,98], lettuce [99], tea [100], watermelon [101], soybean [102], strawberry (Fragaria × ananassa) [103], and citrus [104]. The evaluation of the tomato metabolome was carried out at a previously unprecedented level in a large-scale multiomic study including 610 tomato accessions, extending work on a previous population assembled to gain insight into the processes of tomato domestication and improvement [105].…”
Section: Open Accessmentioning
confidence: 99%
“…Among maize landrace populations, Q ST values measured for ear and flowering traits are significantly higher than F ST values among populations ( 19 ). Q ST – F ST tests also indicate strong divergences for metabolites between wild and cultivated species in maize, tetraploid wheat, and lettuce ( 26 28 ). Perhaps the cause of our somewhat weaker evidence for adaptive divergence among teosinte populations as compared to other wild species is that we assayed traits expected to be important in domestication, and not traits necessarily expected to drive adaption to variation in the natural environment.…”
Section: Discussionmentioning
confidence: 98%
“…While the above studies represent impressive proof-ofconcept studies and additionally greatly refined our understanding of the genotype-to-phenotype interface [16], as we will detail in the following sections it has been adopted in cereal crops (rice [22,54] maize [55,56], wheat [57] and barley [58]) as well as soybean [59][60][61], cotton [62,63], tomato [25,26], cucumber [64,65], sesame [66], peanut [67], peach [68], melon [69], tea [70], and lettuce [71,72]. As we will elaborate in the next four sections, these studies, alongside the purpose-developed populations, catalogs of allelic variants, and corresponding genotype-phenotype associations, provide unprecedented resources for understanding crop functional genomics [33].…”
Section: Early Studies Of Gwas In Arabidopsismentioning
confidence: 99%